The GadX regulon affects virulence gene expression and adhesion of porcine enteropathogenic Escherichia coli in vitro. (June 2017) - Braun, Hannah-Sophie; Sponder, Gerhard; Aschenbach, Jörg R.; Kerner, Katharina; Bauerfeind, Rolf; Deiner, Carolin
Abstract: The ability of enteropathogenic Escherichia coli (EPEC) to express virulence factor genes and develop attaching and effacing (AE) lesions is inhibited in acidic environmental conditions. This inhibition is due to the activation of transcription factor GadX, which upregulates expression of glutamic acid decarboxylase (Gad). Gad, in turn, produces γ-aminobutyric acid (GABA), which was recently shown to have a beneficial effect on the jejunal epithelium in vitro due to increased mucin-1 levels. In the present study, we sought to test whether forced GadX activation/overexpression abolishes virulence associated features of EPEC and provokes increased GABA production. EPEC strains were isolated from diarrheic pigs and submitted to activation of GadX by acidification as well as gadX overexpression via an inducible expression vector plasmid. GABA concentrations in the growth medium, ability for adhesion to porcine intestinal epithelial cells (IPEC-J2) and virulence gene expression were determined. Growth in acidified media led to increased GABA levels, upregulated gadA/B expression and downregulated mRNA synthesis of the bacterial adhesin intimin . EPEC strains transformed with the gadX gene produced 2.1–3.4-fold higher GABA levels than empty-vector controls and completely lost their ability to adhere to IPEC-J2 cells and to induce actin accumulation. We conclude that intensified gadX activation can abolish the ability of EPEC to adhere to the intestinal epithelium by reducing the expression of major virulence genes.